Structural and mechanical properties of (Cr, Ni) N single and gradient layer coatings deposited on mild steel by magnetron sputtering - Bhatti, J.; Fazal, M.A.; Bushroa, A.R.; Khan, A.F.; Quazi, M.M. (Taylor & Francis, 2016)
Ternary single and gradient layer (Cr, Ni) N thin films were deposited on the mild steel substrate by unbalanced magnetron sputtering technique in order to evaluate mechanical properties for machine tools and automotive applications. Microstructure, chemical composition, surface morphology and phase analysis were carried out using field emission scanning electron microscopy, energy dispersive X-ray spectroscopy, atomic force microscopy and X-ray diffraction, respectively. Both single and gradient layer of (Cr, Ni) N coatings show a significant increment in mechanical properties such as hardness, adhesion strength and surface roughness along with the reduction of friction coefficient. Mechanical tests revealed that the hardness of the gradient layer increased up to 3.1 times due to the formation of Cr2N and Ni phase whereas single layer showed the least friction. Single layer CrNiN layer exhibited 27.2% less surface roughness (Ra) in comparison with gradient layer. High values of surface roughness, hardness, thickness and friction could be correlated with high film-to-substrate adhesion (Lc2) for the gradient layer.